Growth of Rice Plant Under Green Light- Inefficient or Neglected (Journal of Environmental Science and Natural Resources, 2022)
The objectives of this study was to investigate the effect of green light-emitting diodes (LEDs) on rice (Oryza sativa L.) seed germination as well as seedling growth. The rice seed of BRRIdhan52, BRRIdhan81, BRRIdhan86 and BRRIdhan92 were germinated and nursed in control environment in full dark (no supplemental light) and under green light (6 h/day with18 h dark). The results showed that germination percent, leaf length, leaf blade length, seedling fresh and dry weight were enhanced by green lighting. Highest germination percent (88%) was counted in BRRIdhan86 and longest first leaf (7.24 cm) with widest leaf (7.24 cm) in BRRIdhan92 under green light. Green light not only enhance the first leaf blade length also increased the dry matter production. High positive significant correlation were observed in seedling fresh weight and dry weight. Correlation value (r) was positive and significantly ranged from 0.999 to 0.981. Green light remarkably promote the leaf surface area, root morphology which ultimately contributed to vigorous seedling growth with an increase 6 to 156 times than rice seedlings grown in dark for the studied character. As a result, the effects of green light emitting diodes (LEDs) on rice seed and seedlings for plant cultivation under controlled-environment conditions are promising, and they may affect subsequent phases of growth and development. More research on green light and other solid state light sources are needed for use in plant lighting designs, as well as the ability to match wavelengths to plant photo sensors for better production and influence on plant morphology and metabolism.Environ. Sci. & Natural Resources, 13(1&2): 50-55, 2020